SMART LIGHTING FOR HOMES IN DENSELY POPULATED AREAS - Santi Febri Arianti (Jurnal Mantik, 2021)
This design was made for densely populated houses with minimal lighting due to poor ventilation. A bottle filled with sodium hypochlorite is mounted on the roof for daytime lighting, so that sunlight will be emitted into the house. A solar cell converts sunlight into electricity, which is stored in a battery and utilized as a source of energy at night. The light sensor will activate the switch when it gets dark and the LED on the bottle will light up, while the sound sensor will recognize clapping to turn the LED off or on. Arduino as a microcontroller and Solar Charge Controller is used to regulate the power that flows from the solar panel to the battery. LCD is selected as the interface to display the amount of energy in the battery. From the data obtained, it can be concluded that the light intensity of the Bottle of Light during the day is greater than 8 Watt lamp. The optimization results show that the optimal charging process is at 3.5 - 4.2 V and the best time for charging is 08:00 - 17:00 WIB. The battery can be used to power the system for 12 hours.